2004
DOI: 10.1086/423270
|View full text |Cite
|
Sign up to set email alerts
|

The Homogeneity of Interstellar Oxygen in the Galactic Disk

Abstract: We present an analysis of high-resolution Hubble Space Telescope (HST ) Space Telescope Imaging Spectrograph (STIS) observations of O i k1356 and H i Ly absorption in 36 sight lines that probe a variety of Galactic disk environments and include paths that range over nearly 4 orders of magnitude in f (H 2 ), over 2 orders of magnitude in hn H i, and that extend up to 6.5 kpc in length. Since the majority of these sight lines have also been observed by the Far Ultraviolet Spectroscopic Explorer (FUSE ), we have … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
146
6

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(168 citation statements)
references
References 54 publications
16
146
6
Order By: Relevance
“…We thus complement the probably most comprehensive benchmark test for stellar atmosphere modelling of OB stars to date Sofia & Meyer (2001); ( f ) value determined from strong-line transitions (Sofia et al 2011), which is compatible with data from the analysis of the [C ii] 158 μm emission (Dwek et al 1997). Weak-line studies of C ii] λ2325 Å indicate a higher gas-phase abundance ε(C) = 8.11 ± 0.07 (Sofia 2004), which corresponds to 84 ± 28 ppm of carbon locked up in dust; (g) Meyer et al (1997), corrected accordingly to Jensen et al (2007); (h) Cartledge et al (2004); (i) Cartledge et al (2006). The uncertainty in the ISM gas-phase abundances is the standard error of the mean; ( j) difference between the cosmic standard and ISM gas-phase abundances, in units of atoms per 10 6 H nuclei; (k) photospheric values of Grevesse & Sauval (1998, GS98), Asplund et al (2009, AGSS09) and Caffau et al (2010, CLSFG10).…”
Section: Global Spectrum Synthesissupporting
confidence: 79%
See 1 more Smart Citation
“…We thus complement the probably most comprehensive benchmark test for stellar atmosphere modelling of OB stars to date Sofia & Meyer (2001); ( f ) value determined from strong-line transitions (Sofia et al 2011), which is compatible with data from the analysis of the [C ii] 158 μm emission (Dwek et al 1997). Weak-line studies of C ii] λ2325 Å indicate a higher gas-phase abundance ε(C) = 8.11 ± 0.07 (Sofia 2004), which corresponds to 84 ± 28 ppm of carbon locked up in dust; (g) Meyer et al (1997), corrected accordingly to Jensen et al (2007); (h) Cartledge et al (2004); (i) Cartledge et al (2006). The uncertainty in the ISM gas-phase abundances is the standard error of the mean; ( j) difference between the cosmic standard and ISM gas-phase abundances, in units of atoms per 10 6 H nuclei; (k) photospheric values of Grevesse & Sauval (1998, GS98), Asplund et al (2009, AGSS09) and Caffau et al (2010, CLSFG10).…”
Section: Global Spectrum Synthesissupporting
confidence: 79%
“…The abundance distributions are very similar, see Fig. 15 for the example of oxygen (the gas-phase abundance distribution is based on 37 diffuse sightlines of Cartledge et al 2004). From this it follows immediately that the dust-phase is chemically also rather homogeneous, what can be expected if mixing processes are highly efficient within the ISM (Sect.…”
Section: Dust Composition Of the Local Ismmentioning
confidence: 58%
“…If we do so, we find that a CLOUDY model with log U % À4:4 gives a generally acceptable fit to the observations for most of the low ions, but with a glaring exception for N i. From the flatness of the predictions for O i and the tight error limits associated with our observation of N(O i), together with the knowledge that O usually is only mildly depleted in the ISM of our Galaxy (Cartledge et al 2001(Cartledge et al , 2004André et al 2003), we may state that the most secure measure of an overall metallicity is given by ½O/H ¼ À0:20 AE 0:07, which represents the distance the measurement is below the model prediction for a solar abundance ratio. The abundances of other elements depend more sensitively on the assumed value for log U.…”
Section: An Initial Choice For the Ionization Parametermentioning
confidence: 59%
“…The IDL 3 routine STISEXTRACT ( Howk & Sembach 2000) was developed in order to reliably estimate the on-order flux background in highresolution (R % 114;000) STIS echelle spectra; experimentation has shown that improvements to the CALSTIS spectral extraction algorithm included with STSDAS now reliably reproduce the central zero-flux level for saturated absorption profiles in the output spectra. However, in the interest of consistency with procedures adopted by Cartledge et al (2001Cartledge et al ( , 2003Cartledge et al ( , 2004 in publishing the krypton and oxygen abundances for these sight lines, STISEXTRACT was used for each E140H observation. The standard CALSTIS extraction algorithm was used for each medium resolution (R % 45;800) exposure.…”
Section: Observations and Data Extractionmentioning
confidence: 99%